Pengaruh Eksitasi Gelombang Iradiasi Ultrasonik Terhadap Kadar Tanin pada Maserasi Biji Pinang Wangi - Rosalina Rosalina; Ferry Ikhsandy; Agung Kurnia Yahya; Hibrah Hibrah (REACTOR: Journal of Research on Chemistry and Engineering, 2021)
Nagari Sikucua, Kampung Dalam Subdistrict, Padang Pariaman produces nearly 800 tons of fragrant areca nut every year which is sent to Jambi to meet export needs. Areca nut contains tannins, substances that have many benefits, some of which are anti-inflammatory, corrosion inhibitors, antioxidants. This study aims to obtain tannins in areca nut extract through a kinetic maceration process with pre-treatment with ultrasonic irradiation wave. The dried areca nut was ground and sieved with various sizes of 20, 40 and 70 mesh and then extracted with ethanol as solvent. The concentration of ethanol used consisted of 35%, 50%, 65% and 80%. Ultrasonic irradiation waves were given for the initial 15 minutes of maceration and then continued with kinetic maceration for up to 4 hours in a water bath at 45°C. The extraction results were concentrated in a rotary evaporator and then tested for tannin levels using Follin Denish reagent in the standard series of tannic acid as a comparison with spectrophotometer UV-Vis. The highest yield of tannin content 11.10% was obtained in the 4-hour maceration process with pre-treatment ultrasonic irradiation at concentration of 80% ethanol with a size of 40 mesh.